Marginal tax rates and tax-favoured pension savings of the self-employed: Evidence from Sweden - Håkan Selin (Uppsala University, Department of Economics, 2009)
In recent years, the study of how individuals respond to policies that aim at promoting pension savings has emerged as a vital area of economic research. This paper adds to this literature by estimating the tax price elasticity of contributions to tax-favoured pension savings accounts on a population of self-employed individuals. I exploit a unique total data base over the Swedish population that covers the years 1999 to 2005. When using instrumental variables I obtain a tax price elasticity estimate of -0.53 and a virtual income elasticity estimate of 0.11, whereas OLS produces estimates that conflict with consumer theory.
urn:nbn:se:uu:diva-161815
Keywords: G23; H24; J33; J26; 330; income taxation; fringe benefits; individual pension savings; self-employment; Selbstständige; Einkommensteuer; Altersvorsorge; Steuervergünstigung; Elastizität; Schweden